Leprosy review - Lehlohonolo Makhakhe (AOSIS, 2021)
Leprosy (Hansen’s disease) can affect multiple organs and body structures. Skin signs are typically observed in the early phase of the disease, hence being the first identifiable signs to propel clinical suspicion. Leprosy predominantly affects the skin and peripheral nerves. The disease has been documented many centuries preceding the biblical era. Over many decades, the classification of Hansen’s disease has changed as modern medical science evolved. Patients with leprosy are usually subjected to discrimination, rejection from society and can suffer from social stigma, poor quality of life (QoL), low self-esteem and permanent disfigurements. Studies have shown that leprosy has a significant negative impact on the patients’ QoL. Leprosy is often not suspected by practicing clinicians because it is no longer emphasised in the medical curricula. In modern years, attention has gradually shifted from leprosy to tuberculosis (TB) and human immunodeficiency virus (HIV).